2001
DOI: 10.1007/pl00021293
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Skills and Growth After One Year of Intraoral Appliance Therapy in Moderately Dysphagic Children with Cerebral Palsy

Abstract: We determined changes in functional feeding skills and growth after one year of intraoral appliance therapy in dysphagic children. Twenty children, 4.2-13.1 years of age (average 8.3 +/- 0.9 years), participated in this study. Children wore the appliance daily. Phase I of treatment (6 months) aimed primarily at stabilizing the mandible and phase II aimed at facilitating ingestive skills. A control period of 6 months preceded treatment. Functional feeding skills improved significantly during phase I beyond chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 0 publications
3
64
0
Order By: Relevance
“…More recent studies show a variety of designs that aim at restoration of speci®c oral skills [24±28]. We have shown that functional feeding skills, as measured by spoon-feeding, biting, chewing, cup drinking, and swallowing (less food and liquid loss), improve signi®cantly after one year of intraoral appliance therapy with an ISMAR [15]. These changes were above the level achieved during a comparable control period.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…More recent studies show a variety of designs that aim at restoration of speci®c oral skills [24±28]. We have shown that functional feeding skills, as measured by spoon-feeding, biting, chewing, cup drinking, and swallowing (less food and liquid loss), improve signi®cantly after one year of intraoral appliance therapy with an ISMAR [15]. These changes were above the level achieved during a comparable control period.…”
Section: Introductionmentioning
confidence: 59%
“…We report results from a two-year study with the following goals: (1) During the ®rst year, the eects of the appliance on jaw stabilization, oral-motor skills, and growth were examined [15]. (2) During the second year, the impact of such therapy on the same outcome measures was to be examined and is the focus of this article.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations